Solutions of a class of singular second-order IVPs by homotopy-perturbation method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Elsevier, 2007)
In this Letter, solutions of a class of singular initial value problems (IVPs) in the second-order ordinary differential equations (ODEs) by homotopy-perturbation method (HPM) are presented. HPM yields solutions in convergent series forms with easily computable terms, and in some cases, yields exact solutions in one iteration. Comparisons with the exact solutions and the solutions obtained by the decomposition method show the potential of HPM in solving singular problems.